Design of Information System in Admission of New Students Based on Web in SMK Al Amanah - Purnomo, Andri Cahyo; Pramono, Bayu; Oganda, Fitra Putri (Pandawan, 2019)
This research has the aim of building a system of acceptance for new students with a website-based method, so that it can help prospective new students in the subject make it easier to obtain information about the registration of new students. Data processing in the acceptance of new students at Al Amanah Vocational School Pasar Kemis still uses Conventional systems, namely prospective registrants come directly to the school then fill out the registration form then the registration data is recorded in a book and reports are made also using manual recapitulation resulting in archival loss and needing a very long time in the process of making a report. Using research methods namely Library Studies, Analysis, Observation, Designing, Trial and Implementation. The information system at the admission of new students is designed using the PHP programming language and using the MySQL database as a Database Server. The output of this research is that the information system on admission of new students with web-based can have the ability to provide convenience for parents of new students in terms of getting all information about acceptance to new students and doing the registration process flow online.